Prevalencia de síndrome de Kelly en pacientes asistentes a la clínica odontológica de la UDLA - Benavides Ronquillo, Karen Jeanneth (2017)
The main objective of this study was to establish the prevalence of Kelly syndrome in patients who attended at the dental clinic of the University of the Americas. Materials and methods: The sample was confirmed by 357 patients, between 18 to 100 years old, who visited the clinic of the Udla in the period March-June, 2017. The prevalence of Kelly syndrome was registered by a survey of my own authorship, in which I observed the presence or absence of Kelly syndrome, in addition to the classes and modifications, in case of presenting the syndrome. As for the results obtained, a prevalence of 45.37 percent was registered, corresponding to 162 patients out of 357, further was observed that the most prevalent class of Kelly syndrome is class one, which corresponds to class IV of Kennedy´s classification and obtained a 51.26 percent, whereas the modification more incident was the modification one that refers to class I of Kennedy obtained 46.77 percent, but in spite of these numbers the combination of more frequent arcades was class one modification one that Obtained 29.97 percent compared to the other combinations.